Natural Entrapments of Killer Whales (Orcinus orca): A Review of Cases and Assessment of Intervention Techniques - Jourdain, Eve; Barrett-Lennard, Lance G.; Ellis, Graeme M.; Ford, John K. B.; Karoliussen, Richard; Towers, Jared R.; Vongraven, Dag (Frontiers in Conservation Science, 2021)
Identifying mortality sources and mitigation solutions is crucial in species management and conservation. In killer whales (Orcinus orca), mortality events may pose a serious concern for the conservation of small discrete populations, especially if they involve entire groups. This study investigated 19 incidents involving 116 killer whales from a minimum of five populations becoming naturally entrapped in inshore areas of the North Pacific (n=12) and North Atlantic (n=7) oceans between 1949 and 2019. Here, we aim to provide an assessment of possible causal factors, lethality and human responses to these events. Site characteristics and group size identified three categories of entrapments. In Category 1, nine cases involved small groups of killer whales (median= 5, range: 1-9) at sites characterized by severe geographic and food constraints. Four cases in Category 2 included larger groups (median= 14, range: 6-19) and entrapment sites with no obvious geographic constraints but at which man-made structures could have acted as deterrents. Five cases assigned to Category 3 involved lone, often young individuals settling in a restricted home range and engaging in interactions with people and boats. Overall, all or some of the killer whales swam out on their own after a mean of 36 d of entrapment (range: 1-172, SD= 51, n=9 cases), died of nutritional/physiological stress after 58 d (range: 42-90, SD=21, n= 3 cases) or of injury after ~five years of daily interactions with boat traffic (n=1 case). Indication of the killer whales’ declining condition or being at risk of injury, and of poor habitat quality, led to the decision to intervene in seven cases where a variety of methods were used to guide or relocate remaining individuals back to open waters after 39 d (SD=51, range=8-150). Monitoring protocols, which aided in identifying entrapment situations, and intervention methods which enhanced the health and survival of entrapped killer whales, are discussed.